2014
DOI: 10.1038/bjc.2014.246
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB3 is associated with TGF-β1 and cytoplasmic β-catenin expression in hepatocellular carcinomas with poor prognosis

Abstract: Background:Hepatocellular carcinoma (HCC) is one of the most important sanitary problems for its prevalence and poor prognosis. To date, no information is available on the prognostic value of the ov-serpin SERPINB3, detected in primary liver cancer but not in normal liver. The aim of the study was to analyse SERPINB3 expression in liver cancer in relation with molecular signatures of poor prognosis and with clinical outcome.Methods:Liver tumours of 97 patients were analysed in parallel for SERPINB3, TGF-β and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 55 publications
12
84
0
Order By: Relevance
“…Recent studies indicate that SerpinB3 is up-regulated by oncogenic Ras, promotes NF-kB-related inflammatory cytokine production 30 and induces IL-6 autocrine signaling 31 , favouring tumour progression. These findings are in keeping with the reported high levels of SerpinB3 detected in the sub-class of HCCs with poor prognosis 32 . A previous study from our group has shown that SerpinB3 is expressed in the majority of hepatoblastomas, where SerpinB3 levels were positively correlated with the extent of Myc expression and tumour diffusion 33 .…”
supporting
confidence: 91%
“…Recent studies indicate that SerpinB3 is up-regulated by oncogenic Ras, promotes NF-kB-related inflammatory cytokine production 30 and induces IL-6 autocrine signaling 31 , favouring tumour progression. These findings are in keeping with the reported high levels of SerpinB3 detected in the sub-class of HCCs with poor prognosis 32 . A previous study from our group has shown that SerpinB3 is expressed in the majority of hepatoblastomas, where SerpinB3 levels were positively correlated with the extent of Myc expression and tumour diffusion 33 .…”
supporting
confidence: 91%
“…The significant impact of SCCA-IgM determination in defining patient prognosis was confirmed also by data showing that SCCA-IgM levels and tumor size were the only identified independent predictors of overall survival [53] . Although these findings must be confirmed in further studies, they are supported by recent data demonstrating that liver tumors with high SCCA-1 tissue expression exhibit higher early recurrence after surgical resection [38] .…”
Section: Scca-igm and Antiviral Treatmentsupporting
confidence: 60%
“…Furthermore, this serpin was identified in the majority of hepatoblastomas, with the highest levels in tumours of more advanced stage [37] . In HCC, high expression of SERPINB3 is significantly associated with early tumour recurrence, and shows a better prognostic significance than other clinical and histological variables [38] . These important clinical findings were confirmed at the mole cular level: SCCA expression in liver tumor has been correlated with liver regeneration activity (expressed by MIB-I-labeling index) [39] , and increased proliferation was also documented in hepatoma cell lines overexpressing SERPINB3 and in a mouse model transgenic for this serpin [39,40] .…”
Section: Sccamentioning
confidence: 97%
“…In addition a very recent study revealed that high levels of SERPINB3 were detectable in 22% of HCCs specimens from cirrhotic patients and were found to be significantly associated with early tumor recurrence, then representing a candidate prognostic marker able to identify the subset of most aggressive HCCs [51]. …”
Section: Implicated Inmentioning
confidence: 99%